For the equation 3x + px + 3-0. p >...
Question
Fullscreen

For the equation 3x + px + 3-0. p > O if one of the roots is square of the other, then pis equal to (A) 1/3 (B) 1 (C) 3 (D) 2/3

JEE/Engineering Exams
Maths
Solution
69
Rating
4.0 (1 ratings)
Fullscreen
Let the roots be ( x ) and ( x^{2} ) By product of roots ( x^{3}=1 ) ( x^{3}-1=0 ) ( (x-1)left(x^{2}-x-1right)=0 ) which implies ( x=1 ) or ( x^{2}-x=-1 ) If we take ( x=1 ) then by sum of roots ( p=-6 ) (but it is rejected as ( p>0 ) ) If we take ( x^{2}-x=-1 ) then by equating with sum of roots ( -1=-p / 3 ) which implies ( p=3 )
Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free